2012
DOI: 10.1016/j.jsv.2012.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the dynamic range of targeted energy transfer in acoustics using several nonlinear membrane absorbers

Abstract: In order to enhance the robustness and the energy range of efficiency of targeted energy transfer (TET) phenomena in acoustics, we discuss in this paper about the use of multiple nonlinear membrane absorbers in parallel. We show this way, mainly thanks to an experimental set-up with two membranes, that the different absorbers have additional effects that extend the efficiency and the possibilities of observation of TET. More precisely, we present the different behavior of the system under sinusoidal forcing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…To date a wide variety of NESs have been proposed and tested: pure cubic spring in mechanical systems [5], membrane acting as cubic or quintic spring in acoustical systems [6], loudspeaker used as a suspended piston acting as an essentially nonlinear oscillator [7]. A numerical work by Gourdon and Lamarque [8] suggests that a NES described by a nonlinear Duffing equation with negative stiffness, acting as a chaotic system, is able to achieve energy pumping for low energy level.…”
mentioning
confidence: 99%
“…To date a wide variety of NESs have been proposed and tested: pure cubic spring in mechanical systems [5], membrane acting as cubic or quintic spring in acoustical systems [6], loudspeaker used as a suspended piston acting as an essentially nonlinear oscillator [7]. A numerical work by Gourdon and Lamarque [8] suggests that a NES described by a nonlinear Duffing equation with negative stiffness, acting as a chaotic system, is able to achieve energy pumping for low energy level.…”
mentioning
confidence: 99%
“…A series of papers [1,2,3,4] demonstrated that a passive control of sound at low frequencies can be achieved using a vibroacoustic coupling between the acoustic field (the primary system) and a geometrically nonlinear thin baffled structure (the nonlinear absorber). In [1,2], the thin baffled structure consists of a simple thin circular visco-elastic membrane whereas in [3,4] a loudspeaker used as a suspended piston is considered.…”
Section: Introductionmentioning
confidence: 99%
“…In [1,2], the thin baffled structure consists of a simple thin circular visco-elastic membrane whereas in [3,4] a loudspeaker used as a suspended piston is considered. In the four papers, theoretical and experimental results are reported considering transient and periodic external excitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear vibroacoustic absorbers have shown their ability to reduce sound especially at low frequencies range and high enough sound field levels. They may thus overcome some limitations of classical devices such as porous materials, Helmholtz resonators, perforated plates [1,2,4,5,6].…”
Section: Introductionmentioning
confidence: 99%